Is the Botryococcus braunii Dry Biomass an Adjuvant for Anti-UVB Topical Formulations? - Maíra Bueno Ariede; Ana Lucia Morocho-Jácome; Thalita Marcílio Candido; Felipe Rebello Lourenço; Edna Tomiko Myiake Kato; Fabiana Vieira Lima; Catarina Rosado; Maria Valéria Robles Velasco; João Carlos Monteiro de Carvalho; André Rolim Baby (MDPI AG, 2020)
Several topical products have been developed to avoid the harmful effects from ultraviolet (UV) radiation, such as sunscreens. Research for actives from natural sources is increasing due to the fact that chemical filters could induce adverse events. The microalgae Botryococcus braunii has potential interest in cosmetic applications. Specialized literature reported that B. braunii aqueous extract induced a reduction in skin dehydration and collagen production and promoted antioxidant activity. This research aimed to produce B. braunii biomass and to investigate its contribution regarding photoprotection. Formulations containing B. braunii dry biomass, with or without UV filters into vehicles composed of an emulsifying polymer or a self-emulsifying base, were evaluated in vitro by means of photoprotective activity and photostability. B. braunii dry biomass did not provide adequate photoprotection efficacy; however, it was observed that the self-emulsifying base promoted better sun protection factor (SPF) in comparison with the emulsifying polymer.